2012
DOI: 10.1074/jbc.m112.341073
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Are Essential for Stretch-induced Vascular Smooth Muscle Contractile Differentiation via MicroRNA (miR)-145-dependent Expression of L-type Calcium Channels

Abstract: Background: miRNAs regulate smooth muscle phenotype. Results: Deletion of miRNAs results in impaired stretch induction of contractile differentiation and reduced expression of L-type calcium channels. Conclusion: miRNAs are crucial for stretch-sensitive smooth muscle differentiation in part via miR-145-dependent expression of L-type calcium channels. Significance: These findings provide novel insights into the mechanism of smooth muscle phenotypic modulation in vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 45 publications
(70 reference statements)
2
77
0
Order By: Relevance
“…The regulation of L-type calcium channel expression by miR-145 is in part mediated by direct interaction of miR-145 with its target CamKII␦ (26,66), which in turn affects the translocation of a transcriptional repressor called DREAM (67). In earlier studies, we found that knockdown of miR-145 or genetic deletion of the miR-143/145 cluster results in increased CamKII␦ expression and reduced expression of L-type calcium channels (26,31,65). Considering the sensitivity to L-type calcium channel verapamil, it is likely that reduced L-type calcium channel expression is involved in the diminished glucose-mediated transcription of contractile smooth muscle markers in miR-143/145 KO cells.…”
Section: No Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of L-type calcium channel expression by miR-145 is in part mediated by direct interaction of miR-145 with its target CamKII␦ (26,66), which in turn affects the translocation of a transcriptional repressor called DREAM (67). In earlier studies, we found that knockdown of miR-145 or genetic deletion of the miR-143/145 cluster results in increased CamKII␦ expression and reduced expression of L-type calcium channels (26,31,65). Considering the sensitivity to L-type calcium channel verapamil, it is likely that reduced L-type calcium channel expression is involved in the diminished glucose-mediated transcription of contractile smooth muscle markers in miR-143/145 KO cells.…”
Section: No Diabetesmentioning
confidence: 99%
“…We have previously demonstrated that actin polymerization is crucial for stretchinduced contractile differentiation in vascular smooth muscle (21)(22)(23)(24). Further, we reported that important regulators of smooth muscle differentiation, such as the small non-coding microRNA miR-145, promotes actin polymerization and that this effect is required for the regulation of contractile smooth muscle genes (25)(26)(27). However, the impact of actin polymerization on smooth muscle gene expression in the context of diabetic vascular disease has not yet been explored.…”
mentioning
confidence: 99%
“…The relative abundance of mRNA was calculated after normalisation to the geometric mean of two internal control genes (Rps29 and Rn18s; Vandesompele et al 2002, Ferguson et al 2010. Qiagen miScript kits, reagents and primers were used to analyse miRNAs (Turczynska et al 2012). Each sample was analysed in duplicates.…”
Section: Rna and Mirna Preparation And Quantitative Real-time Pcrmentioning
confidence: 99%
“…12,84,[92][93][94][95][96][97] Similarly, a large number of microRNAs are implicated in vascular phenotypes ranging from pulmonary hypertension to aortic aneurysm. 77,79,[98][99][100][101][102][103][104][105][106][107] For example, microRNA-145 was recently shown to be upregulated in the lung tissue of patients with pulmonary hypertension and might be a contributing factor to the pathogenesis of pulmonary hypertension. 108 MicroRNA-10, microRNA-15a, microRNA-16, microRNA-26a, microR-NA-223, and microRNA-663 are involved in angiogenesis and regulate vascular smooth muscle and endothelial cell phenotypes.…”
Section: Micrornasmentioning
confidence: 99%